El estudio del reactivo bluestar aplicado a la investigación criminal en la búsqueda de la verdad procesal, con relación al homicidio de la señora Deyanira Lopera Díaz ocurrido en el municipio de San Onofre-Sucre (2014)
"The science of criminology, allows scientifically, corroborating the approach of the theory of the case; and particularly in the proposed topic corresponds to a homicide. The course of criminal investigation and criminology at the Colombian adversarial criminal justice system, through his laboratory at the University La Gran Colombia, raised the case of the murder of a woman, which was abandoned in a suitcase in a dumpster in the municipality of San Onofre - Sucre, so both the respective scientific and technical research begins, to get to the truth procedure established in this research guideline. It starts from the report that holds the first responder, then makes the appropriate delivery to the judicial police officials and scientific technical research that is legal medicine and forensic sciences to each perform the relevant work, starting from inspection to the place, with due photographic record, and proof with BLUESTAR, which is applying the reagent in places and objects where it is suspected to have been the presence of blood and if yes this suspicion ""in a period more or less 10 seconds, a luminous reaction appears evident possessing peroxidase activity blood among other substances ""(anatomiadelcrimen.blogspot.com/2011/07/la-proof-of-BLUESTAR.html.) above in order to give technical or scientific expertise in the expert report that returns results that help direct research in order to obtain the necessary tools to lead us to prove the truth and point out the procedural conduct of the alleged offense (a) murder to so comply as stated in Article 103 and following of the Penal Code of Colombia"